Handbok för växtinsamlare - Ingvarsson, Nina; Norgren, Sofie (2008)
What makes a Swede betake himself into the Chinese wilderness? How does the Rio Convention influence a plant collector? And who will crack the nut positioned 12 meters up in the crown of a tree? There are many secrets behind the act of collecting plants. In many regards, the documentation of the collection of plants for a Swedish purpose has been unsatisfactory. The focus of the publications is on what plant species that have been found rather than information on how these plants have been collected. Only few results of experimental cultivation are available. There is no doubt that there exists knowledge that has not been publicised yet. Sten Ridderlöf, Henrik Zetterlund, Elisabeth Öberg, Magnus Lidén, Björn Aldén and Erland Ejder are all experienced plant collectors who have brought home seed- and plant material for cultivation in Sweden. By using in-depth interviews with these persons, a kind of collection of experience concerning the modern collecting of plants has developed. In the result of the interviews, a manual for plant collectors is presented. Here, a summary of the experiences that emerged from the interviews is given. The manual gives practical advice to anyone who wants to see and collect plants in their natural habitat. In the opening section, the conditions in general for the plant collectors are described. Here, a historical retrospect, role models, interest organisations and other networks is presented. Moreover, a basic description of the legal framework as well as the distribution channels for the collected plant material is given. With our degree project, we would like to contribute in conveying knowledge on the act of collecting plants that up until now only existed in the minds of Sweden's plant pundits.